Women postnatal effects on early and late periods - Gukauskienė, Ligita; Stasiulytė, Sabina (Slauga. Mokslas ir praktika, 2020)
The aim of this study was to investigate the problems of the women in the early and late postnatal periods. The goals of this study: 1. identify the problems of the women early and late postnatal periods; 2. determine the problems of the women, which caused in both postnatal periods; 3. identify the sources of the information for women who are given knowledge about the postnatal periods of the potential problems. Worldwide is the postnatal problems but special attention should be to sadness and depression after the childbirth. Neither sadness nor depression do not affect the baby‘s health but it can cause serious damage to a woman‘s physical and psycho-emotional condition. Women were experienced a lot of problems in the postnatal periods although information can be found online, in print and it provides the health care professionals. The study was included 250 women with postpartum was not less than a year. It was found that only a small percentage of the respondents did not experience the postnatal problems when compared with it suffered. The postnatal period is divided into early and late periods. During these periods, women were experienced different ailments. Especially Caesarean section caused a lot of postnatal problems of the women. In summary, the procreation influences the well-being of the women and their psycho-emotional condition too.
Keywords: females; postpartum problems; postpartum period; health; delivery